2018
DOI: 10.1111/tme.12518
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhaemolysis in a pregnant patient with HbH disease

Abstract: Dear Sir,Hyperhaemolysis is a well-recognised transfusion complication typically described in sickle cell disease (SCD), but it is rarely reported in Haemoglobin H (HbH) disease (Danaee et al., 2014). The increasing incidence of hyperhaemolysis now makes this condition reportable via the UK Serious Hazards of Transfusion scheme (Serious Hazards of Blood Transfusion (SHOT), 2015), and this potentially fatal complication results in challenging management issues in those affected. We present a case of hyperhaemol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Vaeusorn et al (1988)72 reported pre-eclampsia in 18% and congestive heart failure in 9% of 34 pregnancies among 29 Thai women, while in Italy only 5.5% had pre-eclampsia and none had heart failure 2. Aiken et al (2018)73 have recently reported a case of hyperhemolysis in a pregnant patient with Hb H disease who was treated with intravenous methylprednisolone for three days, and 0.4 g kg–1 intravenous immunoglobulins for five days. After six days of post-treatment, the patient’s hemoglobin gradually recovered to her pre-transfusion level of 6.8 g/dL.…”
Section: Delivery Outcomes Of Pregnancies and Breast-feedingmentioning
confidence: 99%
“…Vaeusorn et al (1988)72 reported pre-eclampsia in 18% and congestive heart failure in 9% of 34 pregnancies among 29 Thai women, while in Italy only 5.5% had pre-eclampsia and none had heart failure 2. Aiken et al (2018)73 have recently reported a case of hyperhemolysis in a pregnant patient with Hb H disease who was treated with intravenous methylprednisolone for three days, and 0.4 g kg–1 intravenous immunoglobulins for five days. After six days of post-treatment, the patient’s hemoglobin gradually recovered to her pre-transfusion level of 6.8 g/dL.…”
Section: Delivery Outcomes Of Pregnancies and Breast-feedingmentioning
confidence: 99%
“…Aiken et al . describe a case of hyperhaemolysis in pregnancy where the inherited haemolytic anaemia secondary to HbH disease and transfusion appeared to provide a stimulus for the development of hyperhaemolysis (Aiken et al, ). The case clearly illustrates the typical features of the hyperhaemolysis syndrome, namely, a fall in Hb to lower than pre‐transfused levels, a reticulocytopenia and hyperferritinaemia, often without alloantibodies or a positive DAT.…”
mentioning
confidence: 99%